PENGARUH STRATEGI PEMBELAJARAN INDEX CARD MATCH TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS V SD NEGERI 39 PEKANBARU - Fauziah Fauziah; Syahrilfuddin Syahrilfuddin; Eddy Noviana (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
This study aims to determine the differences in students mathematics learning outcomes in the experimental class using theindex card match learning strategy with the control class using conventional learning. This study uses quasi experimentalmethod with nonequivalent control group design. This design uses two groups, namely the experimental group and thecontrol group. The experimental group is the class that gets treatment while the control group is the class that is not treated.This research was conducted at SD Negeri 39 Pekanbaru in class V. The results of the study based on the experimental classt test and the initial test control class (pretest) that is t_count <t_table or 1.760 <2.016 so that it can be interpreted that thereis no difference. The results of the final test t meet the criteria t count> t table or 2.769> 2.016, which means that there is adifference between the experimental class students and the control class at the final test (posttest). This means that there aredifferences in students mathematics learning outcomes in the experimental class using the index card match learning strategywith the control class using conventional learning. This shows that the index card match learning strategy can affect themathematics learning outcomes of class V students SD Negeri 39 Pekanbaru.